TATA KELOLA PEMBELAJARAN - Abdullah, Maryani Abdullah (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2013)
This study aims at discovering the description on the learning management at SMPN 12 Makassar including the lesson plan, implementation of learning, learning assessment, and the follow-up assessment of learning outcomes.This type of research used in this study is descriptive qualitative. The main source of data in this research field is the Deputy Principal Curriculum, Teacher, Principal and Students. Data collection techniques used were interviews, observation and documentation. The collected data was then analyzed with qualitative methods with the following steps, namely: data collection, data reduction, presenting data, verification of data and concludes the study. The conclusion of the study on the learning management at SMPN 12 Makassar are (i) the lesson plan at SMPN 12 Makassar has been conducted well, (ii) the implementation of learning has been conducted well based on the indicators of learning implementation conducted maximally, (iii) the learning assessment conducted has not been conducted maximally although half of the indicators of learning assessment has been conducted, and (iv) the follow-up of learning assessement conducted has been conducted maximally.